A Creative Approach to Isometries Integrating Geogebra and Italc with 'Paper And Pencil' Environments - Artur Coelho; Isabel Cabrita (European Teacher Education Network, 2015)
Creativity is recognized nowadays as a basic skill. However, the educational system fails in promoting their development. On the other hand, a growing acknowledgement of the importance of geometry emerges. Conceptual renewal, namely on isometries, requires new approaches based on mathematically significant tasks. The digital revolution has brought powerful tools but demands changes in the educational process. The use of Dynamic Geometry Environments (DGE), complementing 'paper and pencil', can contribute to provide rich learning environments, enhanced by Classroom Management Systems (CMS) such as iTALC. Indeed, the qualitative case study we carried out suggests that: the creation of an "atmosphere" of cooperation, collaboration and sharing seems to increase creativity dimensions; the use of DGE can facilitate the emergence of more creative productions; development of knowledge and geometrical capabilities seems to benefit from a complementary approach that combines DGE and 'paper and pencil' environments. Different approaches, with a more technological and exploratory nature seem to promote more favourable attitudes towards mathematics in general, and geometry, in particular.